Біологічні та екологічні особливості Aesculus carnea Hayne та перспективи його використання в озелененні м. Києва - Євтушенко, Юлія Володимирівна (НУБіП України, 2017)
Дисертація на здобуття наукового ступеня кандидата сільськогосподарських наук за спеціальністю 06.03.01 – лісові культури та фітомеліорація. – Національний університет біоресурсів і природокористування України, Київ, 2017. У дисертаційній роботі представлено результати комплексних досліджень екологічних та біологічних особливостей інтродуцента A. carnea в умовах міста Києва. Уперше досліджено особливості насіннєвого та вегетативного способів розмноження A. carnea, охарактеризовано доцільність застосування кожного з них. Підібрано оптимальну технологію мікроклонального розмноження гіркокаштана м’ясо-червоного з метою масового розмноження та отримання рослин-регенерантів. Досліджено сезонний ритм росту і розвитку A. carnea в умовах району досліджень. З’ясовано закономірності проходження фенологічних фаз та їх залежність від метеорологічних показників. Визначено потенційну морозостійкість гіркокаштана м’ясо-червоного за допомогою методу прямого лабораторного проморожування. Встановлено рівень посухостійкості рослин виду в різних екологічних зонах міста Києва. Проведено порівняння отриманих показників вищезазначених екологічних особливостей із гіркокаштаном звичайним та червоним. Визначено функціональний стан фотосинтетичного апарата листків виду в різних урбоекотопах за допомогою методу індукції флуоресценції хлорофілу. Проведено аналіз вмісту важких металів в листках A. carnea та в ґрунті у місцях зростання за допомогою методу атомно-емісійної спектроскопії. На основі отриманих результатів оцінено перспективність рослин виду для садово-паркового будівництва та запропоновано використання декоративних груп за участі A. carnea у системі зелених насаджень міста Києва.
The thesis for awarding scientific degree of candidate of agricultural sciences in specialty 06.03.01 ‒ Forest Plantation and Phitomelioration. ‒ National University of Life and Environmental Sciences of Ukraine, Kyiv, 2017. The thesis presents the results of comprehensive studies of ecological and biological characteristics of introducted species A. carnea in condition of Kyiv. In 1821 A. carnea was first introduced into the territory of the Nikitsky Botanical Garden. Red horse chestnut is included in the species composition of dendroflora of four areas of cultivation (Polesia, Forest steppe, Steppe, Crimea Northern Coast) and grows in the collection of 8 Ukraine botanical gardens, 2 dendroparks and one nature sanctuary. On the basis of the inventory it was established that A. carnea is a rare species in gardening of Kiev, which grows mainly in single and group plantings. In groups grows mainly together with A. hippocastanum, compositions with other trees and shrub species were not observed. Most of the plants ‒ trees at the age from 10 to 20 years. The level of living status was evaluated mostly as «good». Frost cracks, leaves chlorosis and necrosis, branches mechanical damage were the reasons of unsatisfactory plants state. No cases of lesions by horse-chestnut leaf miner (Cameraria orhidella Deschka & Dimic) was not observed, which is a significant advantage compared to A. hippocastanum. Evaluation of decorative signs of studied species allowed characterizing A. carnea as highly decorative species. The features of seed and vegetative propagation methods were studied, the feasibility of each one was described. It was determined that when sowing seed in the second decade of October, without carrying out pre-processing, shoots appear after 176‒182 days. Reproduction by this way is inadvisable, since species is characterized by relatively low reproductive capacity. Results of vegetative propagation by grafting demonstrated feasibility of whip & tongue grafting. The disadvantage of red horse chestnut grafting on common horse chestnut are cases of incompatibility of stock and scion, when there is a predominance of the last one. The optimal technology of red horse chestnut micropropagation for mass reproduction and regenerated plants obtaining was chosen. The fragments of artificially awakened shoots (3‒5 cm long) were used as explants. The optimal scheme of explants sterilization is the using of 1.0 % solution of AgNO3 for 5 minutes. For mass reproduction of A. carnea in culture in vitro it is advisable to cultivate microshoots on MS medium + BAP and kinetin (0.5 mg l-1). Best results of rizogenesis activity were fixed on nutrient medium ½ MS + IBA (5.0 mg l-1). For the first time, seasonal rhythm of growth and development of A. carnea in the conditions of the studied area was investigated. The regularities of the phenological phases passage and their dependence on meteorological parameters were determined. It was established that vegetation of studied species plants begins at the temperature of +6.8...+10.3 °C. On the territory of transport ways with increased levels of stress factors phenological phases are passed for 2‒7 days later compared with areas of M. M. Gryshko National botanic garden and T. G. Shevchenko Park. It was found that the length of species vegetation is 173‒198 days. The potential frost resistance of red horse chestnut was established by the method of direct laboratory freezing. As a result of A. carnea shoots freezing, two-year shoot was the least damaged part and the biggest damage was characteristic for buds. Analysis of the results showed that A. carnea is more cold-resistant than A. hippocastanum. At the same time, negative temperatures damage it more than A. pavia. Damage of studied species shoots caused by exposure of low temperatures was within 15‒40 %, which is not critical for plants. The level of species drought resistance in different ecological zones of Kiev was evaluated. The lowest coefficients of drought resistance were typical for species growing near roadways, the highest ‒ on the territory of M. M. Gryshko National Botanical Garden. Comparison of resistance levels to impact of stress factor of three species of the genus Aesculus showed that A. carnea is more drought-resistant than A. pavia and A. hippocastanum. Red horse chestnut and red buckeye refers to the average drought tolerance species, horse chestnut ‒ to low drought tolerance species. The level of viability and significance of drought resistance coefficient decreases at the transition from M. M. Gryshko National botanic garden to the zone of carriageways on the boulevard Druzhby Narodiv. Under the conditions of the last one, plants feel the increasing of water deficit. The functional state of the photosynthetic apparatus of species leaves in different zones of Kiev using the method of chlorophyll fluorescence induction was determined. It was noted the absence of bacterial and viral diseases. The influence of insufficient insolation on the plants under the conditions of city, that limits the passage of the photosynthesis process, was shown. In the conditions of anthropogenic load increasing, «index of viability» reduced by 25 %, indicating the decrease of intensity of dark photochemical processes in the leaves chloroplasts during the transition from conditional control zone to carriageways. The analysis of the heavy metal content in the A. carnea leaves of and in the soil in areas of growing by atomic emission spectroscopy was conducted. It was demonstrated that on the boulevard Druzhby Narodiv the cuprum total content exceeds the limit, which negatively affects on the life of the plant. The increasing of chromium, iron and zinc content and reduction of manganese in leaves affects on the basic physiological processes in the studied plants. The symptom of chlorosis and premature leaves abscission in the areas of roads, disturbance of intensity of the photosynthesis process is a confirmation of this hypothesis. A. carnea is a perspective species for the introduction to the area of researches. Since red horse chestnut is relatively resistant to the action of stress factors, it is reasonable to use it in landscaping of parks and gardens. For obtaining the decorative compositions the creation of decorative groups with red horse chestnut in combination with other species and cultivars of woody plants according to systematic, ecological, phytocoenotic and physiognomic principles of plants selection were suggested
Keywords: гіркокаштан м’ясо-червоний; інтродукція; інвентаризація; морозостійкість; посухостійкість; індукція флуоресценції хлорофілу; атомно-емісійна спектроскопія; окулірування; копулірування; живильне середовище; культура in vitro; red horse chestnut; introduction; inventory; frost resistance; drought resistance